Ginsenoside Rg1 reverses stress‐induced depression‐like behaviours and brain‐derived neurotrophic factor expression within the prefrontal cortex. (9th May 2016) - Zhu, Xiuzhi; Gao, Rui; Liu, Zhuxi; Cheng, Ziyi; Qi, Yihang; Fan, Cuiqin; Yu, Shu Yan
Abstract: Depression is a major neuropsychiatric disorder that exerts deleterious effects upon public health. However, the neuronal mechanisms of depression remain largely uncharacterized, which has retarded the identification and development of effective therapeutic tools for the treatment of this disorder. The aim of this study was to explore the neuronal mechanisms underlying the protective effects of ginsenoside Rg1, a natural steroidal saponin found in ginseng, against chronic stress‐induced depression.The results showed that chronic administration of ginsenoside Rg1 (40 mg/kg, i.p., 5 weeks) significantly ameliorated depression‐like behaviours in rats as assessed in the sucrose preference and forced swim tests. Furthermore, chronic stress decreased the phosphorylation levels of the extracellular signal‐regulated kinase and cAMP‐response element‐binding protein in the prefrontal cortex as well as producing a reduction of brain‐derived neurotrophic factor expression. Of particular importance, all reductions in these parameters were significantly reversed by pre‐treatment with ginsenoside Rg1. Taken together, the results of the present study suggest that the antidepressant‐like effect of ginsenoside Rg1 might be mediated, at least in part, by activating the cAMP‐response element‐binding protein–brain‐derived neurotrophic factor system within the prefrontal cortex. These findings not only reveal some of the underlying neuronal mechanisms of depression, but also the therapeutic potential of ginsenoside Rg1 as a preventive agent in the treatment of depression. Abstract : We showed that chronic administration of ginsenoside Rg1 significantly ameliorated depression‐like behaviors in chronic unpredictable mild stress (CUMS)‐treated rats, and also dramatically ameliorated the reduction of mature BDNF protein expression as well as the phosphorlyation levels of ERK and CREB in the PFC of these rats. These data indicate that the antidepressant‐like effects of ginsenoside Rg1 might be mediated, at least in part, by activating the CREB‐BDNF system within the PFC.